Study of The Relationship Between Dimensions of Organizational Intelligence and Organizational Entrepreneurship - Hadi Teimouri; Ali Shaemi; Maryam Zarei (مطالعات مدیریت بهبود و تحول, 2017)
According to increase the intensity of competition in the banking sector, retaining existing customers and attracting new customers are very important. Therefore, organizations must have entrepreneurial spirit in the organizational structure and encounter with unstable and dynamic external environment. Intelligent human resources could generate creativity in the turbulent environment and leads to promotion of entrepreneurship in organizations. This study examines the relationship between organizational intelligence and organizational entrepreneurship in branches of Saderat Bank in Isfahan city. To achieve this purpose, the relationship between dimensions of organizational intelligence and organizational entrepreneurship is examined. The study  aim is applied and its nature is descriptive. A self-made questionnaire for collecting data to test the hypothesis questionnaire with acceptable reliability and validity have been used. The research population includes experts and managers of different levels of branches in Saderat Bank in Isfahan city. For sampling, the method of stratified cluster sampling volume concluding the five areas of Saderat Bank in the city is used, Therefor, by random sampling, experts and managers of different levels of bank Isfahan. The sample size, based on Morgan table, is equal to 216 cases and 214 completed questionnaires are analyzed. The results of this study show that there is a significant positive relationship between dimensions of organizational intelligence and organizational entrepreneurship in branches of Saderat Bank in Isfahan city.